2017
DOI: 10.4274/balkanmedj.2016.1256
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Nasopharyngeal Carriage in Young Healthy Children After Pneumococcal Conjugate Vaccine in Turkey

Abstract: Aims: To determine the prevalence of nasopharyngeal carriage of Streptococcus pneumoniae in healthy children aged 0-6 years who were vaccinated with pneumococcal conjugate vaccine.Methods: This cross-sectional study was conducted on 150 healthy Turkish children between 1 month and 6 years of age. Serotyping was performed and risk factors of carriage were evaluated.Results: The overall carriage rate was 14%. Vaccine type serotypes were determined in 17 (12.6%) children who received full-dose PCV13 vaccine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(31 reference statements)
2
11
0
1
Order By: Relevance
“…Erythromycin and clindamycin resistance were 43% and 31%, respectively (12). Correlatively with these results, a study by Arvas et al (2017) also determined that, vaccine type serotypes were detected in 12.6% of children who received full-dose PCV13 vaccine and those strains were found penicillin susceptible with the rates of 85.7% (13). In our study, similar to other studies from Turkey, serogroup 19 and 6 were detected frequently.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Erythromycin and clindamycin resistance were 43% and 31%, respectively (12). Correlatively with these results, a study by Arvas et al (2017) also determined that, vaccine type serotypes were detected in 12.6% of children who received full-dose PCV13 vaccine and those strains were found penicillin susceptible with the rates of 85.7% (13). In our study, similar to other studies from Turkey, serogroup 19 and 6 were detected frequently.…”
Section: Resultssupporting
confidence: 78%
“…vaccine type serotypes were detected in 12.6% of children who received full-dose PCV13 vaccine and those strains were found penicillin susceptible with the rates of 85.7%(13). In our study, similar to other studies from Turkey, serogroup 19 and 6 were detected frequently.…”
supporting
confidence: 89%
“…Current and prior antibiotic use was protective against pneumococcal carriage in some low, upper-middle, and high-income country studies [14, 15, 46, 63, 66, 74-81, 84, 92, 101, 107, 109, 113, 115]. However other studies reported no association between prior antibiotic use and pneumococcal carriage [36,37,40,41,45,47,52,60,70,78,82,93,97,104]. Further, one study reported that antibiotic use in the month preceding the survey was positively associated with carriage, but not at the time of the study [107].…”
Section: Demographicmentioning
confidence: 99%
“…Immunization with the pneumococcal conjugate vaccine (PCV) has substantially reduced NP carriage and invasive pneumococcal disease caused by serotypes represented in the vaccine (12,13). In addition, the introduction of PCV has resulted in a reduction in antimicrobial resistant pneumococci amongst circulating strains due to the inclusion of serotypes associated with high antibiotic resistance in the conjugate vaccine (14).…”
Section: Introductionmentioning
confidence: 99%